Biochemical characterizations of leaves and fruits in Crataegus monogyna Jacq., C. pontica K.Koch, C. microphylla K.Koch, and C. pentagyna Waldst. & Kit. ex Willd - Sama Koliaei; Javad Erfani-Moghadam; Mehdi Saidi; Ali Khadivi; Yazgan Tunç (PLoS ONE, 2026)
The genus Crataegus comprises a diverse group of species with significant medicinal and nutritional value. This study aimed to characterize the biochemical composition of Crataegus monogyna Jacq., C. pontica K.Koch, C. microphylla K.Koch , and C. pentagyna Waldst. & Kit. ex Willd fruits and leaves by evaluating their phenolic profiles, antioxidant capacities, and metabolic interactions. The study also assessed biochemical variations among the analyzed samples and the impact of different ecological conditions on biochemical traits. Descriptive statistical analysis revealed substantial variability in phenolic contents among species. The highest coefficients of variation were observed in ferulic acid (200.00%), flavonol (141.40%), and epicatechin (122.75%). Correlation matrix analysis (CMA) demonstrated strong positive relationships between fruit total phenol and fruit total flavonoid ( r = 0.97*) and between fruit hydroxycinnamic acid and fruit ortho-diphenol ( r = 1.00**), suggesting possible co-accumulation patterns among these metabolites within the analyzed dataset. Exploratory multiple regression analysis (MRA) indicated statistical associations between antioxidant capacity and several phenolic-related variables, including hydroxycinnamic acid, ortho-diphenol, and cinnamic acid within the analyzed dataset. Principal component analysis (PCA) revealed that the first three principal components (PCs) collectively explained 100.00% of the total variance, with PC1 accounting for 71.00%, PC2 for 19.91%, and PC3 for 9.09% of the variation. PC1 was primarily driven by hydroxycinnamic acid, total flavonoid, and total phenol, indicating their important contribution to the observed biochemical separation among the analyzed samples. PCA grouped C. monogyna and C. pontica closely together, whereas C. pentagyna exhibited a distinct profile, particularly in total phenol, total flavonoid, and hydroxycinnamic acid accumulation. Heat map analysis (HMA) classified the species and biochemical variables into distinct clusters, with ‘ C. pentagyna ’ exhibiting a unique metabolic profile, particularly in total phenol, total flavonoid, and hydroxycinnamic acid accumulation. These findings suggest potential biochemical associations between fruit and leaf phenolics, emphasizing the impact of genetic and ecological factors on phenolic metabolism in Crataegus species. The observed associations may provide preliminary information for future breeding-oriented studies aimed at enhancing bioactive compound content for functional food and medicinal applications. Further research integrating transcriptomic and enzymatic analyses is necessary to elucidate the regulatory mechanisms underlying phenolic biosynthesis and environmental adaptability.